STRATEGI SISTEM REKRUTMEN SEKOLAH BERBASIS PENJAMINAN MUTU PENDIDIKAN - Sadarni Sadarni (Institut Agama Islam Negeri (IAIN) Palopo, 2022)
This research aims to find out the strategy of education restruction in schools, one of which is teacher because the quality of education personnel in schools is very dependent on recruitment and selection strategies for interested applicants and to get professional education personnel and have the best quality. Before doing this educator recruitment activity must be really mature so that it can pass the education recruitment process in school as professional educators according to school criteria because it will have an impact on learners. This research method uses this qualitative type of research with library analysis techniques. The result of this study is in improving the quality of education in schools emphasizes how to recruit well, which in the recruitment strategy the quality of education in school is very much but in essence the resources in school education are inadequate. However, in recruitment strategies improving the quality of education in school has been done effectively and a teacher is the main one in education.